2023
DOI: 10.3389/fpsyt.2023.1051542
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis-assisted psychotherapy for complex dissociative posttraumatic stress disorder: A case report

Abstract: BackgroundA dissociative subtype of posttraumatic stress disorder, known as “D-PTSD”, has been included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. In addition to meeting criteria for PTSD, patients endorse prominent dissociative symptoms, namely depersonalization and derealization, or detachment from one's self and surroundings. At present, this population is supported by a highly heterogeneous and undeveloped literature. Targeted interventions are therefore lacking, and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Namely, drug experiences are not seen as treatment side-effects, but rather as essential drivers of potential benefits ( 80 ). While some experts reserve the psychedelic label specifically for agonists of serotonin 2A receptors like psilocybin ( 81 ), psychedelic treatment models have been utilized with diverse psychoactive drugs including MDMA ( 82 ), ibogaine ( 83 ), and cannabis ( 84 ), in addition to ketamine.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, drug experiences are not seen as treatment side-effects, but rather as essential drivers of potential benefits ( 80 ). While some experts reserve the psychedelic label specifically for agonists of serotonin 2A receptors like psilocybin ( 81 ), psychedelic treatment models have been utilized with diverse psychoactive drugs including MDMA ( 82 ), ibogaine ( 83 ), and cannabis ( 84 ), in addition to ketamine.…”
Section: Methodsmentioning
confidence: 99%
“…48 Most recently, a retrospective online survey (n = 160) demonstrated that the reduction in alcohol consumption was significantly associated (p = 0.03) with the intensity of the mystical experience. 49 Furthermore, survey studies demonstrate that the 5-MeO-DMT-induced mystical experience is associated with improvements in symptoms of depression, 47,50 post-traumatic stress disorder (PTSD), 47,51,52 and anxiety. 47,50 This indicates that 5-MeO-DMT could alleviate psychiatric mood-related comorbidities that are highly prevalent in AUD.…”
Section: Potential Therapeutic Mechanisms Of Action Of 5-meo-dmt In T...mentioning
confidence: 99%
“…Furthermore, survey studies demonstrate that the 5‐MeO‐DMT‐induced mystical experience is associated with improvements in symptoms of depression, 47,50 post‐traumatic stress disorder (PTSD), 47,51,52 and anxiety 47,50 . This indicates that 5‐MeO‐DMT could alleviate psychiatric mood‐related comorbidities that are highly prevalent in AUD 92 .…”
Section: Potential Therapeutic Mechanisms Of Action Of 5‐meo‐dmt In T...mentioning
confidence: 99%
“…• Psychedelic Somatic Interactional Psychotherapy (PSIP): Though rigorous trials have not yet been done, we think this method shows particular promise for reducing panic or dissociation that impede typical therapeutic methods [128,126]. In this method, a small dose of THC or ketamine is used to directly engage with, and process, the hyper or hypo-activated defense cascade.…”
Section: Augmenting Mdma-therapymentioning
confidence: 99%